Evaluation of Gamma Irradiation Shielding Performance of Polymer Composites Doped with Chamelea Gallina Shells - Yılmaz, Mücahıt (My University, 2024)
This study investigates the ability of PLA/PEG blend composite materials doped with Chamelea gallina shells to protect against gamma rays. The focus of the study is to determine the effects of increasing the shells ratio on the gamma absorption coeffi-cients. The analyses measured the absorption of gamma rays at both low and high energy levels by these composites. It shows that the gamma absorption coefficient generally increases as the white sand mussel shell content increases. Especially at high ratios (such as 15%) and high gamma energies (1332.51 keV), these materials provide more effective protection at higher energy levels. These findings suggest that shells-enriched polymers can be used as potential radiation shielding materials in areas such as nuclear medicine, radiation therapy, military and space applications. It also supports the potential use of natural materials in the development of radiation shielding materials and offers new avenues for future applications.
Keywords: Chamelea gallina; polymers; composite materials; gamma shielding